Association of long-term exposure to air pollution with sleep among middle-aged and older adults in China: A nationwide study from 2015 to 2018 - Jing Cao; Zirong Li; Yufei Wu; Tian Ni; Jiwei Zhang; Yuying Xu; Zhengchuan Zhu; Miaoran Wang; Qiuyan Li (PLoS ONE, 2026)
Background This study aims to evaluate the associations of long-term exposure to five major air pollutants (PM 2.5 , PM 10 , NO 2 , SO 2 , and CO) with sleep duration and quality among middle-aged and older Chinese adults. Methods This study used data from 14856 adults aged 45 and above participating in the China Health and Retirement Longitudinal Study (CHARLS). Changes in nocturnal sleep duration between baseline (2015) and follow-up (2018) were categorized into three groups: reductions ≥1 h, 1.5 h, or 2 h. The increase in the number of days with restless sleep at follow-up was defined as a deterioration in sleep quality. We used the STET model to estimate air pollution exposure and calculate the concentration differences over 1- or 2-year periods preceding each interview. We investigated the associations of exposure differences to five pollutants with sleep duration and quality through generalized linear mixed and ordinal logistic regression models. Interaction analyses were employed to identify potential effect modifiers. Results All 1-year exposure differences to air pollution positively correlated with reductions in sleep duration of both ≥1.5 h and ≥2 h. CO exposure demonstrated the highest risk for a ≥ 1.5 h reduction (OR = 1.451; 95% CI: 1.065–1.975) and a ≥ 2 h reduction (OR = 1.557; 95% CI: 1.135–2.135) per 1 μg/m 3 increment. Higher exposure levels to PM 2.5 , PM 10, NO 2 and SO 2 correlated with elevated risks of sleep quality deterioration. NO 2 exposure demonstrated the highest risk, with a 22.3% higher risk per 10 μg/m 3 increment (95% CI: 1.039–1.439). Pollutants affected sleep duration and quality in varying temporal patterns. Overall, 1-year exposure difference considerably impacted the sleep duration, while 2-year exposure difference significantly impacted the sleep quality. We also found that the air pollution’s adverse impacts on sleep quality were especially significant for those living in urban areas. Conclusion Long-term exposure to air pollution is associated with adverse sleep outcomes in middle-aged and older populations.